Development of microsatellite markers and analysis of genetic diversity and population structure of Colletotrichum gloeosporioides from Ethiopia - Moges, A.D.; Admassu, B.; Belew, D.; Yesuf, M.; Njuguna, J.; Kyallo, Martina M.; Ghimire, Sita R. (Public Library of Science, 2016)
Twenty three polymorphic microsatellite markers were developed for citrus plant pathogenic fungus, Colletotrichum gloeosporioides, and were used to analyze genetic diversity and population structure of 163 isolates from four different geographical regions of Ethiopia. These loci produced a total of 118 alleles with an average of 5.13 alleles per microsatellite marker. The polymorphic information content values ranged from 0.104 to 0.597 with an average of 0.371. The average observed heterozygosity across all loci varied from 0.046 to 0.058. The gene diversity among the loci ranged from 0.106 to 0.664. Unweighted Neighbor-joining and population structure analysis grouped these 163 isolates into three major groups. The clusters were not according to the geographic origin of the isolates. Analysis of molecular variance showed 85% of the total variation within populations and only 5% among populations. There was low genetic differentiation in the total populations (FST = 0.049) as evidenced by high level of gene flow estimate (Nm = 4.8 per generation) among populations. The results show that Ethiopian C. gloeosporioides populations are generally characterized by a low level of genetic diversity. The newly developed microsatellite markers were useful in analyzing the genetic diversity and population structure of the C. gloeosporioides populations. Information obtained from this study could be useful as a base to design strategies for better management of leaf and fruit spot disease of citrus in Ethiopia.